Tatiana Stepanova as La Sylphide (centre elevated), Michel Panaieff as the Scotsman (centre kneeling), and artists of the company, in Graduation ball, The Original Ballet Russe, Australian tour, His Majesty's Theatre, Melbourne, 1940 (1) - Hall, Hugh P.; Benois, Alexandre, 1870-1960.; Larose, O.; Leiser, A.H.; Lichine, David; Ustinov, Nadia Benois; Antoinette (Firm) (1940)
One of a collection of photographs taken by Hugh P. Hall of 28 ballet productions performed by the Covent Garden Russian Ballet (toured Australia 1938-1939) and the Original Ballet Russe (toured Australia 1939-1940). These are the second and third of the three Ballets Russes companies which toured Australasia between 1936 and 1940. The photographs were taken from the auditorium during a live performance in His Majesty's Theatre, Melbourne and mounted on cardboard for display purposes. For conservation and storage, the photographs have been demounted. The original arrangement of the photographs has been recorded, and details are available from the Pictures Branch of the National Library.
From: Graduation ball : ballet in one act / by David Lichine ; music by Johann Strauss ; compiled, arranged and orchestrated by Antal Dorati.
Inscription: "4C/22".
Part of the collection: Hugh P. Hall collection of photographs, 1938-1940.
Performed April - June 1940.
Choreography by David Lichine ; scenery and costumes by Alexandre Benois ; scenery executed by Nadejda Benois ; ladies' costumes executed by O. Larose and Antoinette ; male costumes executed by A. H. Leiser.
Also available online
Keywords: His Majesty's Theatre (Melbourne, Vic.) -- Photographs; Original Ballet Russe -- Performances -- Photographs; Graduation ball (Choreographic work) -- Photographs; Ballet dancers -- Photographs; Ballet -- Australia -- Photographs; Ballets Russes in Australia